Effectiveness of the 30-Degree Lateral Sleeping Position on Sleep Quality in Elderly Individuals Post-Stroke - Priastana, I Ketut Andika; Agustini, Ni Rai Sintya (Basic and Applied Nursing Research Journal, 2023)
Background: Post-stroke conditions can have an impact on the sleep quality of the elderly. Sleep disorders are a common health problem for the elderly, requiring serious attention. Poor sleep quality in the elderly is caused by increased sleep potential, reduced sleep efficiency, and early awakenings due to the ageing process. Objective: This research aims to determine the effectiveness of a 30-degree lateral sleeping position compared to a supine sleeping position on the sleep quality of elderly individuals post-stroke. Method: The design of this research uses a quasi-experiment design with a non-equivalent control group design approach. The study will be conducted in 2023 in Ekasari Village, Jembrana Regency, Bali. The total research population is 126 elderly individuals, and the sample size meeting the criteria is 64 respondents, divided into 32 respondents in the intervention group and 32 respondents in the control group. Data analysis in this study uses the Mann-Whitney U Test. Results: The Mann-Whitney U Test shows a difference between the intervention and control groups (p = 0.000, Z score = -4.830), which means that the 30-degree lateral sleep position is better at helping older people who have had a stroke sleep better than the supine sleep position. Conclusion: Post-stroke elderly individuals tend to experience an improvement in sleep quality when they sleep in the lateral position of 30 degrees. Therefore, elderly people who are having sleep quality issues can adopt this sleeping position to improve their sleep.